PARADIGMA ISLAMISASI ILMU DALAM INTEGRASI AGAMA DAN SAINS PERSPEKTIF ISMAIL RAJI AL-FARUQI - Fajri Perdana Putra; Zahqy Muliana; Ikhwanul Aulya; Amril M; Liana Novita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study discusses the integration of religion and science in the perspective of Ismail Raji al-Faruqi through the concept of Islamization of knowledge. The purpose of this study is to analyze the concept of tauhid as the foundation of Islamic epistemology in developing the integration of religion and science. This research uses a qualitative approach with a library research method by examining books, journals, and related literature on al-Faruqi’s thoughts. The results of the study show that tauhid in al-Faruqi’s perspective is not only understood as a theological concept, but also as a principle that integrates knowledge, life, and history. According to al-Faruqi, science should not be separated from moral and spiritual values because all knowledge ultimately comes from Allah SWT. Therefore, the Islamization of knowledge is considered an effort to reconstruct modern science so that it remains connected to Islamic values. This study also finds that the dichotomy between religious and secular sciences is still a challenge in modern education systems. In this context, al-Faruqi’s concept of tauhid can become an alternative framework in building a holistic and integrative scientific paradigm that combines rational, empirical, moral, and spiritual dimensions.